Size effect at aggregate level in microCT scans and DEM simulation – Splitting tensile test of concrete - Suchorzewski, J.; Nitka, M. (Engineering fracture mechanics, 2022)
•Experimental and numerical study of size effect on concrete in splitting tensile test.•The post-peak behavior of all tested specimens including catastrophic behavior (snap-back).•Cracked specimens scanned with micro-CT to study fracture process.•DEM model based on microCT scans with realistic meso-structure.•DEM results captured size/effect on strength and post-peak behavior including snap-back. The paper describes an experimental and numerical study of size effect on concrete cylindrical specimens in splitting tensile test. Own experimental campaign was performed on specimens with 5 various diameters from D = 74, 105, 150, 192 and 250 mm with hardboard loading strips (distributed load according to standard methods) scaled proportionally to the specimen diameter. The crack opening-control system was applied to obtain the post-peak behaviour of all tested specimens including catastrophic behaviour (snap-back). The tested specimens at a certain point were unloaded and scanned with novel high-resolution micro tomography to analyse the macro cracks and phenomena like aggregate breakage, crack branching etc. at the aggregate level. Based on realistic mesostructure the discrete element method (DEM) 2D model of 3 specimens with diameters of D = 74, 150 and 250 mm were constructed and tested. The fracture was analysed at macro and micro-level in DEM and directly compared with microCT scans. DEM simulations revealed additional information related to the loss of material strength and ductility with increasing specimen size (size effect). The simulation and experimental results were in good agreement.